6.7. Solutions Recursive Definitions#

Solutions to Section 3.7

Solution to Exercise (1†)

Proof: We prove this once again by induction.

  • Base Case: When \(n = 0\) and when \(n = 1\), the statement is clearly true, since \(f_0 = 0 < 1 = 2^0\) and \(f_1 = 1 < 2 = 2^1\), so \(f_0 < 2^0\) and \(f_1 < 2^1\).

  • Inductive Case: If we now take an arbitrary \(k\) such that \(k \geq 2\), we assume that \(f_n < 2^n\) for \(n = k-1\) and \(n = k-2\) holds. To complete the induction, we need to show that \(f_k < 2^k\) is also true:

    \[\begin{split}\begin{align*} f_k &= f_{k-1} + f_{k-2} \\ &< 2^{k-1} + 2^{k-2} &\textnormal{(inductive hypothesis)} \\ &= \frac{2^{k}}{2} + \frac{2^{k}}{4} \\ &= \frac{3}{4} \cdot 2^k \\ &< 2^k \end{align*}\end{split}\]

    This shows that \(f_k < 2^k\) is true, which completes the induction.

Solution to Exercise (2†)

Proof: We prove the equation using induction.

  • Base Case: When \(n = 1\), \(a_1 = 1\cdot2^{1-1}\) is true since both sides are equal to 1.

  • Inductive Case: Let \(k \geq 1\) be an arbitrary integer. We asssume that \(a_n = n2^{n-1}\) holds for \(n = k-1\). To complete the induction, we need to show that the equation also holds for \(n = k\).

    \[\begin{split}\begin{align*} a_k &= 2a_{k-1} + 2^{k-1} \\ &= 2(k-1)2^{k-1-1} + 2^{k-1} &\text{(inductive hypothesis)} \\ &= (k-1)2^{k-1} + 2^{k-1} \\ &= ((k-1)+1)2^{k-1} \\ &= k2^{k-1} \end{align*}\end{split}\]

    Which proves that the equation also holds for \(n=k\). Thereby the induction is completed.